Quantification of cellular autofluorescence of human skin using multiphoton tomography and fluorescence lifetime imaging in two spectral detection channels - Patalay,R; Talbot,C; Alexandrov,Y; Munro,I; Neil,MAA; Koenig,K; French,PMW; Chu,A; Stamp,GW; Dunsby,C (Biomedical Optics Express, 2011)
We explore the diagnostic potential of imaging endogenous fluorophores using two photon microscopy and fluorescence lifetime imaging (FLIM) in human skin with two spectral detection channels. Freshly excised benign dysplastic nevi (DN) and malignant nodular Basal Cell Carcinomas (nBCCs) were excited at 760 nm. The resulting fluorescence signal was binned manually on a cell by cell basis. This improved the reliability of fitting using a double exponential decay model and allowed the fluorescence signatures from different cell populations within the tissue to be identified and studied. We also performed a direct comparison between different diagnostic groups. A statistically significant difference between the median mean fluorescence lifetime of 2.79 ns versus 2.52 ns (blue channel, 300-500 nm) and 2.08 ns versus 1.33 ns (green channel, 500-640 nm) was found between nBCCs and DN respectively, using the Mann-Whitney U test (p < 0.01). Further differences in the distribution of fluorescence lifetime parameters and inter-patient variability are also discussed.